THE DECISION USEFULNESS OF FINANCIAL ACCOUNTING MEASUREMENT CONCEPT - Soegeng Soetedjo (Journal of Economics, Business, and Accountancy Ventura, 2012)
The objectives of financial reporting are to provide the accounting information to investors,creditors, and other external users conducting the investment or other economic decision. Thefirm assets and liabilities show the real economic objects and must be presented in monetaryterm. Yet, the accounting measurement concept of assets and liabilities in this case are themain problem in financial accounting. For that reason, it is important for practitioners, accountingstandard setter, and academician to understand the accounting measurement conceptclearly. This study analyzes the influence of the investors/analysts understanding on the accountingmeasurement concept, length of experience, type of financial service industry, type oftransaction instrument, and character of the job for decision making on the basis of accountingmeasurement concept. Beside, it also provides inputs to accounting standard setter regardingthe role of accounting measurement concept in decision making by user of accounting information,especially investors. The result indicate that the decision making based on accountingmeasurement concept generally to be considered to invest and is influenced directly by understandinginvestor/analyst on the accounting measurement concept, length of experience, type offinancial service industry, type of transaction instrument, and characteristic of the job.